2008
DOI: 10.1093/jee/101.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance of Resident Parasitoids and Predatory Flies and Corresponding Soybean Aphid Densities, with Comments on Classical Biological Control of Soybean Aphid in the Midwest

Abstract: Seasonal abundance of resident parasitoids and predatory flies, and corresponding soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), densities were assessed in soybean fields from 2003 to 2006 at two locations in lower Michigan. Six parasitoid and nine predatory fly species were detected in 4 yr by using potted plants infested with soybean aphid placed in soybean fields. The parasitoid Lysiphlebus testaceipes Cresson (Hymenoptera: Braconidae) and the predatory flies Aphidoletes aphidimyza Rondani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…A. obliqua is also a well-known aphidophagous flower fly with potential as BCA (Smith and Chaney, 2007;Noma and Brewer, 2008;Hopper et al, 2011) but immature stages of both Allograpta species are not yet distinguishable using morphology (Arcaya, 2012).…”
Section: Life Table Studymentioning
confidence: 99%
“…A. obliqua is also a well-known aphidophagous flower fly with potential as BCA (Smith and Chaney, 2007;Noma and Brewer, 2008;Hopper et al, 2011) but immature stages of both Allograpta species are not yet distinguishable using morphology (Arcaya, 2012).…”
Section: Life Table Studymentioning
confidence: 99%
“…In China and the Eastern United States, both generalist predators and more specialized parasitoids are important (van den Berg et al 1997;Liu et al 2004;Wu et al 2004b;Miao et al 2007;Nielsen and Hajek 2005;Hajek et al 2007;Wu, Heimpel and Hopper, unpublished data;see below). In the NorthCentral US, however, parasitoids have little impact on A. glycines (Lin and Ives 2003;Rutledge et al 2004;Costamagna and Landis 2006;Kaiser et al 2007;Noma and Brewer 2008;Noma et al 2010) and at least one predator that is present in Eastern N. America (A. muelleri) is absent from soybean fields (see below). In Asia, parasitism rates ranging between 45 and 52% were routinely recorded over a 5 year period in Jilin province (Gao 1994), one of the principal soybean producing areas.…”
Section: Buckthorn and Soybean Aphidmentioning
confidence: 99%
“…A number of both native and introduced predators, parasitoids and pathogens have been documented consuming the soybean aphid since its introduction in North America in 2000 (e.g. Rutledge et al 2004;Nielsen and Hajek 2005;Mignault et al 2006;Kaiser et al 2007;Chacon et al 2008;Noma and Brewer 2008) and the presence of soybean aphid could lead to enrichment of any of these species. Such enrichment could lead to a number of indirect ecological effects, chief among these being apparent competition, where an increase in abundance of a consumer of one species leads to increased consumption of one or more different species (Holt and Lawton 1994).…”
Section: Soybean Aphid As a Facilitator Speciesmentioning
confidence: 99%
“…While parasitoids appear to have a more prominent role in controlling soybean aphid populations in eastern Asia (Liu et al, 2004;Wu et al, 2004;Miao et al, 2007), several native and previously established parasitoids have been found to attack soybean aphids in North America (Kaiser et al, 2007;Noma and Brewer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A. colemani was introduced in the early 1990s to control the Russian wheat aphid in North America and has subsequently become established at several locations. A. colemani has been shown to attack soybean aphid in the field (Lin and Ives, 2003;Kaiser et al, 2007;Noma and Brewer, 2008). In part because of its preference for attacking larger aphids and its ability to control soybean aphid population growth rates (Lin and Ives, 2003;Chacón et al, 2008), A. colemani has been considered as a potential biological control agent of the soybean aphid.…”
Section: Introductionmentioning
confidence: 99%